ANALISIS PENERIMAAN PEMBAYARAN LISTRIK PASKA BAYAR DAN PRABAYAR TERHADAP PENDAPATAN PT. PLN di NGAWI - Nurul Janahti; Isharijadi Isharijadi (Universitas PGRI Madiun, 2013)
The purpose of this study was to determine how the effectiveness of the receipt of payment postpaid and prepaid electricity to earnings PT. PLN in Ngawi. Type of research by the author is a qualitative descriptive study, the type of data the author was interviewing, observation and data analysis methods are collected, compiled, interpreted, analyzed, thus providing a complete description. Based on the research conducted, the authors conclude that the effectiveness tinggkat between postpaid and prepaid electricity in 2011 was still effective prepaid electricity, but for greater earnings power postpaid. For postpaid electricity ineffective due each month PT. PLN UPJ Ngawi suffered losses from delinquent customers and for prepaid electricity more effectively but the amount of prepaid electricity customers still small. Contributions related electric revenue postpaid and prepaid electricity PT.PLN UPJ Ngawi more profitable prepaid electricity, because of the effectiveness of the payment easier to use a prepaid system, it is also proportional to the increased number of prepaid subscribers in 2011.